2020
DOI: 10.3390/ijerph17020480
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and Waterborne Pathogen Emergence in Low-Income Countries: Where and How to Conduct Surveys?

Abstract: A major forthcoming sanitary issue concerns the apparition and spreading of drug-resistant microorganisms, potentially threatening millions of humans. In low-income countries, polluted urban runoff and open sewage channels are major sources of microbes. These microbes join natural microbial communities in aquatic ecosystems already impacted by various chemicals, including antibiotics. These composite microbial communities must adapt to survive in such hostile conditions, sometimes promoting the selection of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 158 publications
(173 reference statements)
0
12
0
Order By: Relevance
“…While in most regions of the world’s oceans we do not expect a relevant colonization of microplastics with potentially pathogenic taxa, the risk might be higher in strongly anthropologically impacted areas. A great amount of plastic waste worldwide enters the oceans at coastal sites with high populations, often situated at estuaries with dynamic conditions, and close to waste water drainage systems, such that an enhanced dissemination of potentially pathogenic bacteria on plastics poses a realistic threat to these communities [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…While in most regions of the world’s oceans we do not expect a relevant colonization of microplastics with potentially pathogenic taxa, the risk might be higher in strongly anthropologically impacted areas. A great amount of plastic waste worldwide enters the oceans at coastal sites with high populations, often situated at estuaries with dynamic conditions, and close to waste water drainage systems, such that an enhanced dissemination of potentially pathogenic bacteria on plastics poses a realistic threat to these communities [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence and dissemination of antimicrobial resistance (AMR) is an increasingly serious threat to global public health (WHO, 2015;Qiao et al, 2018;Thomas et al, 2020), that has turned into an emergency in lowincome countries (Bastaraud et al, 2020). Consequently, a significant reduction in the effectiveness of antibiotics and other antimicrobial agents (antifungals, antivirals, antimalarials, and anthelmintics) threatens our ability to treat common infectious diseases, resulting in prolonged illness, disability, and death (Wright, 2010;Almakki et al, 2019).…”
Section: Water Quality Assessment: Antimicrobial Resistance As a Global Threat To Public Healthmentioning
confidence: 99%
“…Recently, flow cytometry and 16S rRNA sequencing have shown that silver nanoparticles (AgNPs) clearly affect the microbial community structure and suggest a potential negative impact on WWTP functions (Guo et al, 2019). Finally, given the increased presence of microplastics as aquatic emerging water pollutants, their role as potential vectors for harmful microbes and propagation of ARBs and ARGs is a matter of growing concern (Bastaraud et al, 2020;Song et al, 2020;Zhang et al, 2020).…”
Section: Water Quality Assessment: Antimicrobial Resistance As a Global Threat To Public Healthmentioning
confidence: 99%
“…(i) use multi-OMIC and interdisciplinary approaches to understand the role of the plastisphere in plastic biodegradation as well as in determining the mechanisms and pathways used for biodegradation 19,151,157,161,164,170,172,175,178,180,181,183,184,188,189,191,194,196,[198][199][200][204][205][206][207] ;…”
Section: Discussionmentioning
confidence: 99%
“…Other taxa that are not generally regarded as invasive, toxic or pathogenic as such, but that can cause nuisance via mucilage events, such as the diatom species Ceratoneis closterium 83 have also been reported as plastisphere members. Alongside the potential toxicity of the plastic polymer itself, or plastic additives and sorbed contaminants (as reviewed recently by Pham et al 207 ), plastics' potential to be considered harmful clearly also depends on the interaction with pathogens and non-native taxa present in the environment (see above), especially in polluted environments such as wastewater effluents and water bodies in the proximity of densely populated urbanised areas 180 .…”
Section: Effects Of Microbe-plastic Interactions On Plastic Buoyancy and Transportmentioning
confidence: 99%